2011
DOI: 10.1103/physreva.84.053406
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modification of the fragmentation of autoionizing states of O2+

Abstract: The dynamic process of fragmentation of excited states of the molecular oxygen cation is investigated in a two-part study. First, using monochromatic 41.6 eV radiation and cold-target recoil-ion momentum spectroscopy detection of O + + O + ion pairs and associated electrons, we establish that this channel is populated only by an indirect process enabled by autoionization of excited oxygen atoms and identify the final active potential curves. Second, we probe the dynamics of this process using an attosecond pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…A grating-based monochromator consisting of a pair of identical holographic blazed gratings (3600 lines=mm) followed by a slit is installed after the harmonic generation cell, allowing the selection of the 11th harmonic (∼17 eV). The other part of the laser pulse energy is combined with the 11th harmonic pulse to form a MachZehnder interferometer [15]. Both the 11th harmonic pulse and the IR probe pulse are focused independently onto the gas target in a reaction microscope [16,17].…”
mentioning
confidence: 99%
“…A grating-based monochromator consisting of a pair of identical holographic blazed gratings (3600 lines=mm) followed by a slit is installed after the harmonic generation cell, allowing the selection of the 11th harmonic (∼17 eV). The other part of the laser pulse energy is combined with the 11th harmonic pulse to form a MachZehnder interferometer [15]. Both the 11th harmonic pulse and the IR probe pulse are focused independently onto the gas target in a reaction microscope [16,17].…”
mentioning
confidence: 99%
“…The rapid development of laser technology, ultrashort vacuum ultraviolet (VUV), and extreme ultraviolet (XUV) sources in combination with advanced detection techniques, such as momentum imaging spectroscopy, has opened new opportunities for unraveling and controlling ultrafast molecular dynamics of nonequilibrium systems [1][2][3][4][5][6][7]. Recent studies showed how femtosecond VUV and XUV radiation can be used to reveal transient nuclear and electron dynamics in diatomic molecules [8][9][10][11][12] as well as in more complex molecular systems [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the attosecond to few-femtosecond nature of the HHG radiation forms a temporally localized excited state wavepacket whose dynamics can be followed in real-time using a time-delayed probe [5][6][7][8][9]. Recently experiments have employed these attosecond XUV sources to study ultrafast fragmentation [10] and autoionization [11,12] in highly excited molecular ions.…”
mentioning
confidence: 99%